Relationship between Madrasah Culture and Innovative Attitude and Madrasah Ibtidaiyah Negeri Teachers' Work Commitment - Telaumbanua, Idam Shaleh; Arsyad, Junaidi; Nahar, Syamsu (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The goal of this research was to discover the relationship between madrasah culture and teacher work commitments in Madrasah Ibtidaiyah Negeri Gunung Sitoli, the relationship between innovative attitudes and teacher work commitments in Madrasah Ibtidaiyah Negeri Gunung Sitoli, and the relationship between Madrasah culture and innovative attitudes in Madrasah Ibtidaiyah Negeri Gunung Sitoli teachers. people, using a random sample from the entire population or total sampling A questionnaire with a Likert scale model was used as the research instrument. The requirements test was used to determine the independence, linearity, and normality of the independent variables. At a significance level of = 0.05, the data analysis technique used correlation and regression, as well as simple correlation and regression and multiple correlations. According to the findings of the study, there is a positive and significant relationship between madrasa culture and teacher work commitment. This means that the higher and more positive the madrasa culture, the higher and more positive the work commitment of the teachers of Gunung Sitoli City's State Islamic Madrasah by providing an effective contribution of 8.5 percent. Innovative attitudes and teacher work commitment have a positive and significant relationship. This means that the higher and more positive the innovative attitude, the higher and more positive the work commitment of the Madrasah Ibtidaiyah teachers throughout the city of Gunung Sitoli by providing an effective contribution of 4.56 percent, and there is a positive and significant relationship between madrasa culture and innovative attitudes in general. This means that the higher and more positive the madrasa culture and innovative attitude, the higher and more positive the work commitment of the teacher.